A four‐year survey on unexpected pregnancy diagnoses in a large urban emergency department in Parma, Italy. Issue 1 (29th May 2014) - Cervellin, Gianfranco; Comelli, Ivan; Sartori, Elisabetta; Lippi, Giuseppe
Abstract: Objective: To investigate the rate of unexpected pregnancy diagnoses in the emergency department of the Academic Hospital of Parma, Parma, Italy. Methods: Data for all patients with a positive β‐human chorionic gonadotropin test between October 2008 and September 2012 were retrieved from the hospital records. Information on age, gender, country of birth, and reason for presenting to the emergency department was collected. Results: During the study period, 160 151 visits of female patients were recorded, including 385 (0.2%) women who received a diagnosis of pregnancy; 97 (25.2%) were native Italians and 288 (74.8%) were foreign‐born. The percentage of women presenting for trauma did not differ between the two groups, whereas the rate of admission to the obstetrics and gynecology department was higher among natives (20.6% vs 9.0%; P = 0.002). Africans represented 66.0% (n = 190) of the women with an unexpected pregnancy diagnosis. Nigerians accounted for 20.8% (n = 60) of all foreign‐born women with a pregnancy diagnosis, although they represented less than 2% of the entire immigrant population. Conclusion: Unexpected pregnancy is a problem in the province of Parma, most notably among women from Sub‐Saharan Africa. Efforts should be strengthened to provide more fragile groups with easily available family planning information.